Pemanfaatan Teknologi Marketing Dan Inovasi Produk Terhadap Keunggulan Bersaing Untuk Meningkatkan Kinerja Pemasaran - Ayu Feranika; Despita Meisak; Maria Rosario Borroek; Muthia Hanum (Akademi Akuntansi YKPN Yogyakarta, 2023)
This study aims to empirically prove the effect of using social media and product innovation on competitive advantage to improve marketing performance. This research is a quantitative research with data analysis tools used Structural Equation Modeling (SEM) in the AMOS 2.6 program. The results of this study prove and conclude that marketing technology and product innovation have an effect on competitive advantage, and competitive advantage has an effect on marketing performance. Theoretically, this study confirms that there is a positive relationship between factors that influence competitive advantage, namely the use of marketing technology and product innovation, as well as a positive relationship between competitive advantage and marketing performance, where the findings in this study support many similar research results.Competitive advantage plays a role in improving marketing performance, to increase competitive advantage it is necessary to utilize marketing technology and innovate products.